Water accessibility as a catalyst for food diversity: a case study - Ronen Eliraz, Gefen; Aviram, Ariel; Mendelsohn, Opher; Avisar, Dror (Frontiers in Water, 2025)
Integrated knowledge of the interlinkage between water access and food security is essential for informing future intervention strategies. This study evaluates the role of physical water infrastructure in providing safe drinking water, and its impact on the dietary diversity within rural communities in the Dodoma region of Tanzania. By comparing households in communities with and without water-intervention projects, finding demonstrates that proximity to water sources significantly enhances dietary outcomes. The level of nutrition for the communities with and without water-intervention projects were evaluated by food consumption score (FCS) and dietary diversity score (DDS). A decreasing trend of FCS and DDS with an increase in the time needed to fetch water indicated a significant negative correlation (Spearman's correlation analyzing all participants = −0.178, p < 0.001 and −0.221, p < 0.001, respectively). Households near water resources had higher FCS and DDS than those farther away, suggesting that water supply infrastructure projects enhance both sustainable water and nutrition goals.